A 130‐year global inventory of methane emissions from livestock: Trends, patterns, and drivers. (20th June 2022) - Zhang, Lei; Tian, Hanqin; Shi, Hao; Pan, Shufen; Chang, Jinfeng; Dangal, Shree R. S.; Qin, Xiaoyu; Wang, Siyuan; Tubiello, Francesco N.; Canadell, Josep G.; Jackson, Robert B.
Abstract: Livestock contributes approximately one‐third of global anthropogenic methane (CH4 ) emissions. Quantifying the spatial and temporal variations of these emissions is crucial for climate change mitigation. Although country‐level information is reported regularly through national inventories and global databases, spatially explicit quantification of century‐long dynamics of CH4 emissions from livestock has been poorly investigated. Using the Tier 2 method adopted from the 2019 Refinement to 2006 IPCC guidelines, we estimated CH4 emissions from global livestock at a spatial resolution of 0.083° (~9 km at the equator) during the period 1890–2019. We find that global CH4 emissions from livestock increased from 31.8 [26.5–37.1] (mean [minimum−maximum of 95% confidence interval) Tg CH4 yr −1 in 1890 to 131.7 [109.6–153.7] Tg CH4 yr −1 in 2019, a fourfold increase in the past 130 years. The growth in global CH4 emissions mostly occurred after 1950 and was mainly attributed to the cattle sector. Our estimate shows faster growth in livestock CH4 emissions as compared to the previous Tier 1 estimates and is ~20% higher than the estimate from FAOSTAT for the year 2019. Regionally, South Asia, Brazil, North Africa, China, the United States, Western Europe, and Equatorial Africa shared the majority of the global emissions in the 2010s. South Asia, tropical Africa, and Brazil have dominated the growth in global CH4 emissions from livestock in the recent three decades. Changes in livestock CH4 emissions were primarily associated with changes in population and national income and were also affected by the policy, diet shifts, livestock productivity improvement, and international trade. The new geospatial information on the magnitude and trends of livestock CH4 emissions identifies emission hotspots and spatial–temporal patterns, which will help to guide meaningful CH4 mitigation practices in the livestock sector at both local and global scales. Abstract : Using the Tier 2 method adopted from the 2019 Refinement to 2006 IPCC guidelines, we estimated annual methane emissions from global livestock at a spatial resolution of 0.083° (~9 km at the equator) during the period 1890−2019. Our results indicated a fourfold increase in global livestock methane emissions in the past 130 years, showing much faster emissions in developing regions than in developed regions.